2015
DOI: 10.1111/jop.12385
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of cyclooxygenase‐2 (COX‐2) in oral nevi and melanoma

Abstract: COX-2 is highly positive in oral melanomas and negative in oral nevi and might represent a useful marker to distinguish melanocytic lesions of the oral cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
2
12
1
Order By: Relevance
“…Here we utilised this system to show that, in the context of canine melanoma, COX-2 is required for cellular proliferation, migration and invasion. Previous studies, consistent with our data, have shown that, by immunohistochemical analysis of COX-2, there is a significant association between COX-2 levels and the proliferation status of cells within a tumour cell population (5,7,29,31). Several studies have also revealed the inhibition of COX-2 by NSAIDs and COXIBs leads to a dosedependent reduction in cell proliferation in a range of cancer cell lines (15,(36)(37)(38).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here we utilised this system to show that, in the context of canine melanoma, COX-2 is required for cellular proliferation, migration and invasion. Previous studies, consistent with our data, have shown that, by immunohistochemical analysis of COX-2, there is a significant association between COX-2 levels and the proliferation status of cells within a tumour cell population (5,7,29,31). Several studies have also revealed the inhibition of COX-2 by NSAIDs and COXIBs leads to a dosedependent reduction in cell proliferation in a range of cancer cell lines (15,(36)(37)(38).…”
Section: Discussionsupporting
confidence: 92%
“…Previously, overexpression of COX-2 has been correlated with the development and progression of human cutaneous melanoma (29,30) and has been proposed as a prognostic marker. In oral melanoma, COX-2 is highly expressed but negative in oral nevi indicating that COX-2 is a valuable marker to distinguish melanocytic lesions of the oral cavity (31), and elevated COX-2 expression is correlated with poor prognosis (32). Similarly, in canine melanoma COX-2 levels are related to Ki-67 proliferation index and survival rate indicating that COX-2 is related to the acquisition of malignancy (7,16,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…They conclude that differentiation of cyclooxygenase-2 expression in more detail would help to delineate when cyclooxygenase can be defined a negative prognostic factor. Others demonstrated cyclooxygenase-2 to be a useful immunohistochemical marker for the differentiation of melanoma from benign melanocytic lesions in the oral cavity (19). Among others, these observations substantiate findings that suggest cyclooxygenase-2 expression and/or activity as both a pathogenic key player and a promising molecular target in melanoma (20).…”
Section: Cyclooxygenase-2supporting
confidence: 69%
“…Furthermore, two studies found that the level of COX-2 in mucoepidermoid carcinoma (MEC) was strongly increased, whereas most of the pleomorphic adenomas and adenoid cystic carcinomas (AdCC) were COX-2-negative [46,47]. In melanomas, Nascimento et al found that oral melanomas were consistently COX-2-positive compared with the benign oral nevi, which were completely COX-2-negative [48]. However, in another study on odontogenic tumors, both the benign and the malignant tumors expressed COX-2, however, the malignant amelocarcinoma specimens exhibited higher levels of COX-2 compared with the benign ameloblastoma samples.…”
Section: Cox-2 Expression In Other Head and Neck Tumorsmentioning
confidence: 99%